Life101 Enhances Healthy Lifestyle Choices in Pre-Health Undergraduate Students - Jafari, Mahtab (Journal of University Teaching and Learning Practice, 2017)
Stress levels in college students are increasing at an alarmingly fast pace. To combat this rising tide, universities need effective tools to promote student well-being and help them to recognize and manage their stress. One approach is to teach students basic lifestyle skills to cope with stress and achieve wellness. This is important as it not only increases students’ retention within a chosen field of study, but assists them to achieve personal and academic success. To inspire our undergraduate students to adopt healthy lifestyle choices, a once-weekly course titled “Life101” was developed with topics that focused on students’ wellness such as stress management, emotional intelligence, financial management, nutrition, and exercise. Classes were taught through a combination of lecture, multimedia videos, and discussions. Here, we share our observational findings outlining the potential benefits (short- and long-term) for students participating in Life101. Based on pre- and post-course survey data from students, both in-class and online, Life101 had a significant positive impact on the lifestyle of our students. The main outcomes from this study were: 1) both in-class and online courses resulted in positive lifestyle changes in our students; 2) online students showed greater mastery of course topics compared to their in-class peers; and 3) long-term benefits from the course were reported after a one-year follow-up. Although, this collective positive impact may suggest that offering Life101 to undergraduate students can serve to improve students’ mental and physical health, a prospective study is needed to confirm these findings.